Lower limbs kinematic analysis during a jump landing task in soccer players with unilateral anterior cruciate ligament reconstruction - Moosareza Ghorbani; Hamed Nouri; Mona Heydarian; Mohammad Mottaghitalab; Hamed Zarei (BMC, 2024)
Abstract Background Fatigue leads to an acute decline in muscle strength, altered patterns of lower extremity muscle activation, changes in hip and knee kinematics. In terms of the effects of fatigue on knee joint kinematics during plyometric training, there is still a lack of knowledge regarding kinematic differences between athletes who passed the ACL reconstructions rehabilitation period and healthy athletes. Therefore, this study aimed to compare lower limb joint kinematic parameters between reconstructed cruciate ligament and healthy control soccer players during jump landing in a fatigued setting. Methods Lower limb kinematic parameters were recorded in 20 professional soccer players (age, 24.95 ± 2.92 years; body mass, 77.20 ± 12.88 kg; height, 1.77 ± 3.19 m) during jump landing task before and after the fatigue protocol. The control group consisted of healthy subjects and the experimental group consisted of subjects with ACL reconstruction by thigh transplantation. Kinematic data was recorded with 4 cameras to measure lower limb angles at first foot contact and maximum range of motion. Results The results showed that before fatigue, there was only a significant difference between the two groups in the maximum range of motion of the non-involved hip joint (P = 0.022) and angle of the involved hip at first contact (P = 0.049). In other data on joint range of motion or initial contact angle, no significant difference was observed between the two groups (P > 0.05). After fatigue protocol, there was a significant difference in initial foot contact in non-involved (P = 0.030), and involved (P = 0.020) hip joint angles between the two groups. However, no significant difference in initial contact angle or range of motion of other joints was observed between the groups. Conclusions This study shows that plyometric fatigue does not contribute to numerous changes in contact angles and range of motion in lower extremity joints in healthy soccer players and those with a history of cruciate ligament repairs.